Possíveis relações entre competências de cálculo mental e iniciação algébrica de alunos de 6º e 7º anos do Ensino Fundamental - Figueiredo, Thereza Maria de Fátima Quilici (2013)
The present paper is part of the research group Desenvolvimento curricular em Matemática e formação de professores (Curricular development in Math and teacher s formation , specifically in the project A aprendizagem significativa e conhecimentos prévios: investigando o currículo de matemática, em uma perspectiva construtivista (Meaningful learning and previous knowledge: researching the Math curriculum, in a constructivism perspective). It aims to identify, understand and characterize previous knowledge of the 6th and 7th grade students in relation to mental calculus and how this knowledge is associated with the construction of tasks that are usually presented with the goal of inserting it in the area of algebra. It is a qualitative research conducted with thirteen students, being seven of a 6th grade group and six of another 7th group, all of them from a private school in São Paulo city. The students took part in two activities. The first one had the objective of researching procedures of mental calculus used by the students to make calculus involving both natural numbers as well as rational numbers in a decimal form. The second activity had the intention of rising procedures used by these students to perform some tasks, that may be presented to students of the 7th grade, that characterize their first approaches with calculus using letters. In the end of the analysis, we noticed that the competence revealed by the students related to the mental calculus with natural numbers contributed in a positive way for the exploring of the algebra situations presented, that shows the importance of using this knowledge as support. Thus, we notice that these students were able to solve algebra problems using their arithmetic knowledge, without the formal use of algebra manipulation. We could also realize this is not verified for calculus with rational numbers in a decimal form, due to the difficulties related to these numbers